Kalimatu “Qarîb” Fî Al-Qurân ‘Inda Fakhruddin Al-Razi Fî Al-Tafsir Al-Kabir - Ilham Habibullah; Abdullah Muhammady (Universitas Darussalam Gontor, 2019)
The word “Qarib” is an adjective in Arabic Language, Al-Quran used and declared that Allah is close to His servants, but Al-Quran also declared that Allah turned above the “arsy” which is located above the seventh heaven. In other contexts, Al-Quran declared that the Day of Judgment is close, while the revelation has passed 14 centuries but Judgment Day has not yet occurred. Therefore what is the concept of Allah closeness to His servants? And Judgment Day closeness? This research examined these concept in Al-Tafsir Al-Kabir written by Fakhruddin Al-Razi. By adopting the objective interpretation as theoretical framework. it used two approaches, Descriptive Method and Analytical Method to collect the data in analyzing them. The conclusion is Allah's closeness according to Al-Razi is not related to the place, but he interpreted it with the Knowledge of Allah, also in the context of philosophy, the Creator is the intermediary between the Essence of beings and his Being, then the Creator is closer to the essence than his own being. The closeness of Judgment Day is interpreted in three points. First, it implied the threat of Allah that the Judgment Day will come suddenly. Second, the time remaining in the world was less than what has already happened, third, the Judgment Day was easy for Allah